Beef, Casein, and Soy Proteins Differentially Affect Lipid Metabolism, Triglycerides Accumulation and Gut Microbiota of High-Fat Diet-Fed C57BL/6J Mice - Ijaz, Muhammad Umair; Ahmed, Muhammad Ijaz; Zou, Xiaoyou; Hussain, Muzahir; Zhang, Min; Zhao, Fan; Xu, Xinglian; Zhou, Guanghong; Li, Chunbao (Frontiers in Microbiology, 2018)
Consumption of dietary protein at recommended levels is considered a potential strategy to promote satiety and weight management, but how protein from different dietary sources effect the obesity development, lipid metabolism, and gut microbiota is not known. This study focused on the effects of beef, casein and soy protein diet on lipid metabolism, triglycerides accumulation and microbial diversity in colon of C57BL/6J mice, which were given either low fat diets (LFD, 12 % Kcal) or high-fat diets (HFD, 60% Kcal) for 12 weeks. Body and liver weight increased significantly in mice fed a beef protein high fat-diet (HFB), whereas reduced cumulative energy intake was seen in a soy protein high-fat diet (HFS) group. HFB-fed mice showed signs of impaired glucose metabolism and insulin resistance along with a significant elevation in the concentration of triglycerides, LDL-cholesterol, total cholesterol, IL1β, TNF-α, IL-6, and leptin in serum. HFB also enhanced lipid accumulation in liver with increased activity of genes important for lipogenesis and hepatic cholesterol metabolism. A 16S rRNA gene sequencing indicated that HFD, regardless of proteins, significantly enhanced the ratio of Firmicutes to Bacteroidetes in colonic microbiota. However, HFB not only reduced the abundance of Akkermansia, compared with LFD independent of proteins, but also decreased the abundance of butyrate-producing bacteria such as Anaerotruncus, Butyricicoccus and Lactobacillus (P < 0.05) compared with HFS and HFC. In conclusion, consumption of HFB does not only affect the gut microbiota composition, but also increases the problems related to metabolic syndromes like dyslipidemia, Hypercholesterolemia, and triglycerides accumulation in liver which lead to systemic inflammation and its associated comorbidities e.g. impaired glucose metabolism and insulin resistance.